The course syllabus a learning-centered approach - O'Brien, Judith Grunert (Jossey-Bass higher and adult education series, 2008)
When it was first published in 1997, The Course Syllabus became the gold standard reference for both new and experienced college faculty. Like the first edition, this book is based on a learner-centered approach. Because faculty members are now deeply committed to engaging students in learning, the syllabus has evolved into a useful, if lengthy, document. Today's syllabus provides details about course objectives, requirements and expectations, and also includes information about teaching philosophies, specific activities and the rationale for their use, and tools essential to student success.